2015
DOI: 10.1017/s0033291715000276
|View full text |Cite
|
Sign up to set email alerts
|

A computational analysis of flanker interference in depression

Abstract: Background Depression is characterized by poor executive function, but—counterintuitively—it is associated with highly accurate performance on certain cognitively demanding tasks. The psychological mechanisms responsible for this paradoxical finding are unclear. To address this issue, we applied a drift diffusion model (DDM) to flanker task data from depressed and healthy adults participating in the multi-site Establishing Moderators and Biosignatures of Antidepressant Response for Clinical Care for Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 62 publications
(97 reference statements)
4
51
1
Order By: Relevance
“…Here we show that sequential sampling models can be fit to decision data from the MOT to reveal underlying decision strategies used by different groups. Further, since prior research has tended to focus on investigating cognitive deficits within certain populations, rather than proficiencies (e.g., Dillon et al, 2015;Forstmann et al, 2011;Heathcote et al, 2015;van Ravenzwaaij et al, 2012), it was opportunistic to model the decision strategies and processes from a tightly selected group of RAAF personnel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we show that sequential sampling models can be fit to decision data from the MOT to reveal underlying decision strategies used by different groups. Further, since prior research has tended to focus on investigating cognitive deficits within certain populations, rather than proficiencies (e.g., Dillon et al, 2015;Forstmann et al, 2011;Heathcote et al, 2015;van Ravenzwaaij et al, 2012), it was opportunistic to model the decision strategies and processes from a tightly selected group of RAAF personnel.…”
Section: Discussionmentioning
confidence: 99%
“…With sequential sampling methods often enabling a deeper understanding of the decision making process and underlying strategy, we proposed an experiment which tested two divergent groups on varying levels of MOT. A large proportion of modelling studies that compare across groups have tended to focus on cognitive deficits associated with certain groups (e.g., aging populations; Forstmann et al, 2011;, schizophrenia;Heathcote et al, 2015;and depression;Dillon et al, 2015) rather than a "proficiency". However, our study aimed to compare a student control group to a group of highly trained Royal Australian Air Force (RAAF) personnel as a means of understanding potential differences in cognitive decision making processes.…”
Section: Motmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have suggested that drift rate is the DDM parameter that reflects stimulus congruency (Dillon et al 2015; Pe et al 2013; White et al 2011). However, in those studies, the decision threshold was not allowed to vary with stimulus congruency, and hence, it could not predict stimulus congruency.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies showed that incongruent stimuli were associated with a lower drift rate than congruent stimuli (Dillon et al 2015; Pe et al 2013; White et al 2011), but in none of these studies the threshold was allowed to account for congruency effects. In another study where the decision threshold was allowed to vary between conditions (King et al 2012), this parameter accounted for congruency effects.…”
Section: Introductionmentioning
confidence: 99%